ULVA COMPRESSA MARINE EXTRACT ORCHESTRATES ANTI-INFLAMMATORY AND ANTIPROLIFERATIVE ACTIONS IN HUMAN COLON AND LIVER CANCER CELLS: IN VITRO STUDY - Khulud M. Alshehri (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
Background: Colorectal and hepatocellular carcinomas remain leading contributors to global cancer mortality, and current therapeutic strategies offer limited long-term success. Cisplatin (CP), despite being a widely used frontline chemotherapeutic, is frequently hindered by severe organ toxicity and the rapid emergence of resistance. With the growing interest in marine-derived therapeutics, algae have gained prominence as a source of biologically active compounds with demonstrated anticancer and anti-inflammatory actions. In this study, we examine the cytotoxic, apoptosis-inducing, and anti-inflammatory properties of Ulva compressa (UC) extract in HCT-116 colorectal carcinoma and HepG2 hepatocellular carcinoma cells, with cisplatin serving as a benchmark drug. Methods: Cytotoxicity was evaluated using the sulforhodamine B (SRB) assay, while microscopic examination was used to monitor treatment-induced morphological alterations. Apoptotic and necrotic cell populations were quantified via Annexin V-FITC/PI flow cytometry, and cell cycle distribution was analyzed using propidium iodide staining. Gene expression of Bax and Bcl-2 was assessed through quantitative real-time PCR, and protein expression of PI3K-p85α and mTOR was determined by Western blotting. Anti-inflammatory activity was measured in LPS-stimulated RAW 264.7 macrophages by quantifying nitric oxide (NO) via the Griess reaction. Total antioxidant capacity and intracellular glutathione (GSH) levels were quantified using commercial enzymatic kits. Statistical significance was assessed using one-way ANOVA with Tukey’s post-hoc test. Results: UC extract significantly and progressively reduced the viability of both cancer cell lines, with HepG2 cells showing greater susceptibility. Microscopy corroborated the cytotoxic changes. Flow cytometry confirmed notable increases in early apoptosis and sub-G1 accumulation. qRT-PCR demonstrated enhanced Bax expression with concurrent Bcl-2 suppression, while Western blotting revealed marked downregulation of PI3K-p85α and mTOR. Additionally, the extract exhibited potent anti-inflammatory activity by reducing NO production and elevating antioxidant capacity and intracellular GSH. In conclusion: Ulva compressa ethanolic extract exhibited strong anticancer potential against HCT-116 and HepG2 cells, performing comparably to cisplatin yet demonstrating a broader and more favorable mechanistic profile. UC extract robustly activated intrinsic apoptotic pathways (Bax/Bcl-2) as well as components of the extrinsic cascade (cleaved caspase-8/tBid/TNFR1), promoted significant sub-G1 accumulation, and effectively suppressed PI3K/mTOR signaling while inducing minimal necrosis. In contrast, cisplatin primarily imposed G2/M cytostasis, exhibited lower apoptotic induction, and caused more necrotic damage. Overall, Ulva compressa presents an equally effective but potentially safer therapeutic alternative, with higher selectivity and a more apoptosis-dominant mode of action.